2018
DOI: 10.18203/2349-2902.isj20180343
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical patterns in benign breast disorders

Abstract: Background: This is a prospective study aimed at evaluating patients presenting with breast related complaints at Dr. D.Y. Patil Medical College, Pimpri, Pune. It outlines various clinical patterns in benign breast disorders; this includes age, type of presentation, side and quadrant of breast involved, size of breast lump and the eventual diagnosis.Methods: A prospective study was conducted at Dr. D.Y. Patil Medical College, Pimpri, Pune, between July 2016 and July 2017. Author evaluated 50 patients, male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 5 publications
(5 reference statements)
4
10
0
Order By: Relevance
“…[4][5][6][7] In the present study, lump in the breast was the most common presentation in 60% of patients, of which more than half patients had a lump with pain; however, 12 patients presented with only pain with no other signs and symptoms, and five male patients presented with gynecomastia. These results were generally similar to previous studies where the presenting symptom was lump in the breast in 58% (Tonape et al), [8] 58.06% (Singh et al), [9] 72.35% (Ratanachaikanont et al), [10] and 87.4% (Foncroft et al). [11] In the present study, benign breast diseases was the highest in the age group of 21 to 30 years (43.08%), which was consistent with previous study by Tonape et al (42%) [8] and Das et al (45%), [12] however, in another study by Kapur et al, the highest number of benign breast diseases were found in age group of 31 to 40 years (31.6%), followed by 21 to 30 years (31.1%) and 11 to 20 years (27.3%).…”
Section: Parameterssupporting
confidence: 91%
See 3 more Smart Citations
“…[4][5][6][7] In the present study, lump in the breast was the most common presentation in 60% of patients, of which more than half patients had a lump with pain; however, 12 patients presented with only pain with no other signs and symptoms, and five male patients presented with gynecomastia. These results were generally similar to previous studies where the presenting symptom was lump in the breast in 58% (Tonape et al), [8] 58.06% (Singh et al), [9] 72.35% (Ratanachaikanont et al), [10] and 87.4% (Foncroft et al). [11] In the present study, benign breast diseases was the highest in the age group of 21 to 30 years (43.08%), which was consistent with previous study by Tonape et al (42%) [8] and Das et al (45%), [12] however, in another study by Kapur et al, the highest number of benign breast diseases were found in age group of 31 to 40 years (31.6%), followed by 21 to 30 years (31.1%) and 11 to 20 years (27.3%).…”
Section: Parameterssupporting
confidence: 91%
“…These results were generally similar to previous studies where the presenting symptom was lump in the breast in 58% (Tonape et al), [8] 58.06% (Singh et al), [9] 72.35% (Ratanachaikanont et al), [10] and 87.4% (Foncroft et al). [11] In the present study, benign breast diseases was the highest in the age group of 21 to 30 years (43.08%), which was consistent with previous study by Tonape et al (42%) [8] and Das et al (45%), [12] however, in another study by Kapur et al, the highest number of benign breast diseases were found in age group of 31 to 40 years (31.6%), followed by 21 to 30 years (31.1%) and 11 to 20 years (27.3%). [13] In another study by Singh et al, aberrations in normal development and involution of the breast were highest reported in the age group 21 to 30 years and 31 to 40 years (36.36% each) and breast lump was highest reported in 21 to 30 years group (52.77%).…”
Section: Parameterssupporting
confidence: 91%
See 2 more Smart Citations
“…Breast masses have a wide diversity of etiologies, commonly benign cause, fibrocystic changes are the most common breast disorder, while fibro adenoma is the most common benign breast mass; invasive ductal carcinoma is the most common malignancy (Gaaib et al, 2014;Tonape et al, 2018). The risk of breast cancer rises with age.…”
Section: Introduction:-mentioning
confidence: 99%